2020
DOI: 10.3390/ijms21113915
|View full text |Cite
|
Sign up to set email alerts
|

How TRPC Channels Modulate Hippocampal Function

Abstract: Transient receptor potential canonical (TRPC) proteins constitute a group of receptor-operated calcium-permeable nonselective cationic membrane channels of the TRP superfamily. They are largely expressed in the hippocampus and are able to modulate neuronal functions. Accordingly, they have been involved in different hippocampal functions such as learning processes and different types of memories, as well as hippocampal dysfunctions such as seizures. This review covers the mechanisms of activation of these chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 171 publications
1
16
0
Order By: Relevance
“…Studies have indicated that TRP channels, ubiquitously expressed throughout the brain, 10 play a key role in the regulation of physiological functions, as well as in pathological ones, including cardiovascular, neurological, metabolic, or neoplastic disorders. [6][7][8]41,42 Moreover, mutations in genes encoding TRP channels are the cause of several inherited diseases in humans (the so-called 'TRP channelopathies') that affect the cardiovascular, renal, skeletal, and nervous systems. 43 Since TRP channels can be opened and activated in response to various stimuli, their hyperactivation can induce neuronal loss and excitotoxicity, which are closely associated with neurodegenera- tive diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have indicated that TRP channels, ubiquitously expressed throughout the brain, 10 play a key role in the regulation of physiological functions, as well as in pathological ones, including cardiovascular, neurological, metabolic, or neoplastic disorders. [6][7][8]41,42 Moreover, mutations in genes encoding TRP channels are the cause of several inherited diseases in humans (the so-called 'TRP channelopathies') that affect the cardiovascular, renal, skeletal, and nervous systems. 43 Since TRP channels can be opened and activated in response to various stimuli, their hyperactivation can induce neuronal loss and excitotoxicity, which are closely associated with neurodegenera- tive diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they are involved in the basic hippocampal function, such as different memory and learning processes. 7 TRP ions channels family is involved in sensory (pheromone signaling, taste transduction, nociception, and temperature sensation) and homeostatic functions (such as Ca 2+ and Mg 2+ reabsorption and osmoregulation), as well as muscle contraction and vasomotor control. Their dysfunction contributes to the etiology of several diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Based on structure–function relationships, the TRPC family is grouped into four subsets: TRPC1, TRPC2, TRPC3/6/7 and TRPC4/5. Besides functioning as homotetramers, combinations of different TRPC subunits can form heterotetrameric complexes, which may regulate responses to neuropeptides and neurotransmitters with different properties than homotetrameric TRPC channels [ 28 ]. For instance, TRPC6 has high sequence homology with TRPC3 and TRPC7 subunits, and may form a heterotetramer with TRPC3 [ 29 ].…”
Section: Trpc6mentioning
confidence: 99%
“…Based on struc-ture-function relationships, the TRPC family is grouped into four subsets: TRPC1, TRPC2, TRPC3/6/7 and TRPC4/5. Besides functioning as homotetramers, combinations of different TRPC subunits can form heterotetrameric complexes, which may regulate responses to neuropeptides and neurotransmitters with different properties than homotetrameric TRPC channels [28]. For instance, TRPC6 has high sequence homology with TRPC3 and TRPC7 subunits, and may form a heterotetramer with TRPC3 [29].…”
Section: Trpc6mentioning
confidence: 99%